Coping is not enough! : the international debt crisis and the roles of the World Bank and International Monetary Fund - Miller, Morris (Homewood, Ill. : Dow Jones-Irwin, 1986)
The book analyzes the nature and examines the profound changes of recent decades that underlie the United States abandonment of the Bretton Woods Agreement and the emergence of the global debt crisis. The author focuses on the roles of International Monetary Fund and World Bank, a "new Bretton Woods", the Banker Initiative and efforts to achieve economic coordination.
Includes bibliographical references and index.
rpm 23/08/16
Loans
Keywords: Debts, External; International finance; World Bank; International Monetary Fund; Debt Management; Developing countries